2021
DOI: 10.3171/2020.12.spine201908
|View full text |Cite
|
Sign up to set email alerts
|

Clinical outcomes in revision lumbar spine fusions: an observational cohort study

Abstract: OBJECTIVE The authors compared primary lumbar spine fusions with revision fusions by using patient Oswestry Disability Index (ODI) scores to evaluate the impact of the North American Spine Society (NASS) evidence-based medicine (EBM) lumbar fusion indications on patient-reported outcome measures of revision surgeries. METHODS This study was a retrospective analysis of a prospective observational cohort of patients who underwent elective lumbar fusion between January 2018 and December 2019 at a single quatern… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 44 publications
1
15
0
Order By: Relevance
“…We found that the VAS scores of these patients remained higher than those who did not undergo the second procedure at the final follow-up, which was consistent with the results of previous studies [7,18]. In a retrospective study of 309 patients, Montenegro et al [19] found that up to 23% of patients had a declined functional status 6 months after reoperation. The underlying reason for this is unclear; however, more extended hospital stays and higher costs may lead to lower satisfaction and confidence in the operation [20,21].…”
Section: Discussionsupporting
confidence: 91%
“…We found that the VAS scores of these patients remained higher than those who did not undergo the second procedure at the final follow-up, which was consistent with the results of previous studies [7,18]. In a retrospective study of 309 patients, Montenegro et al [19] found that up to 23% of patients had a declined functional status 6 months after reoperation. The underlying reason for this is unclear; however, more extended hospital stays and higher costs may lead to lower satisfaction and confidence in the operation [20,21].…”
Section: Discussionsupporting
confidence: 91%
“…A subset analysis was also conducted to evaluate exclusively patients who had just 2 surgeries (the primary procedure and the revision) (n = 65) to evaluate whether the addition of multiple procedures might have influenced the results, but the findings were analogous to what was demonstrated with the full dataset. The median ODI improvement of the group of patients who had a revision with a different surgeon (median: 10; IQR, [3][4][5][6][7][8][9][10][11][12][13][14] was significantly greater than the group who had a revision with the same spine surgeon (median: 4; IQR, -2 to 11) (P = .031). Moreover, the percentage of patients from the different group who achieved ODI MCID (68.5%) was also significantly higher than the same group (43.3%) (P = .041) in this subset analysis.…”
Section: Resultsmentioning
confidence: 99%
“…As seen in previous literature, patient specific factors such as preoperative ODI, ASA class, and classification of revision surgery demonstrated statistical correlations with PRO in the form of MCID at 6 months postoperatively. 29,34 Of note, patient factors traditionally predictive of increased morbidity such as age, 35 BMI, 36 and smoking status 37 did not improve outcome modeling as they did not significantly contribute to differences in PRO in this cohort. This is likely When examining surgeon experience, this study confirmed that MCID in ODI improvements postoperatively were statistically correlated with the surgeon's years in practice.…”
Section: Discussionmentioning
confidence: 78%